High molecular weight glucose homopolymer of broccoli (Brassica oleracea var. italica) stimulates both invertebrate and mammalian immune systems - Miyashita, Atsushi; Kataoka, Keiko; Tsuchida, Toshio; Ogasawara, Akihiko Ano; Nakajima, Hiroto; Takahashi, Megumu; Sekimizu, Kazuhisa (Frontiers in Food Science and Technology, 2023)
There is widespread interest in the immunostimulatory effects of food-derived substances that are expected to contribute to improving human health. Broccoli (Brassica oleracea var. italica) has been shown to contain potent polysaccharides for developing food materials with immunomodulatory function. In this study, immunostimulatory activity of previously uncharacterized broccoli polysaccharides was assessed using a silkworm (Bombyx mori) immunological assay (using muscle contraction as an index) across 10 commercial and 17 experimental cultivars of broccoli. For the commercial cultivars, there was a significant variation in specific activity (units/mg, measured by the silkworm-based immunological assay). For the experimental cultivars, a cultivar “winter dome” showed the highest activity. We further purified the immunostimulatory polysaccharides of “winter dome” by gel filtration. Using the silkworm-based assay, we found that the peak fraction (“Fraction II”) contained the active substance with higher specific activity than previously reported active substances (e.g., glucans). The substance appeared a heterogeneous molecular weight of more than 270 kDa. The major sugar composition of Fraction II was glucose, suggesting that glucose homopolymer is responsible for the activity. Further, Fraction II induced cytokine productions both in the silkworm (production of active B. mori paralytic peptide (BmPP) in vivo) and mouse (production of TNFα in vitro) immune system. These results suggest that glucose homopolymer of broccoli induces cytokines both in insect and mammalian immune systems, providing molecular insights to our understanding about how plant-derived substances interact with animal immune system.